Hubungan Motivasi Kerja Dengan Kinerja Pegawai di Lingkungan Parusahaan Daerah Air Minum Pemerintah Kota Sukabumi - Asep Apudin (BUANA INFORMATIKA CBI, 2016)
Motivation Relationships Work With Employee Performance in the Regional Water Environment Government company Sukabumi The research was conducted at the Environmental PDAM Sukabumi City Government, in order to determine Motivation Relationships with Corporate Environmental Performance Officer at the Regional Water Sukabumi City Government. The research sample using statistical data analysis, sample size was 30 respondents were chosen at random (random) with consideration of the large number of employees and the principle of representation of the number of employees In this election based on level of education, and employee groups are done intentionally (purposive) due not all employees have the free time to fill out a questionnaire and were interviewed, based on the results of the study it can be concluded the discussion as follows: The correlation value of r = 0.708, meaning that the effect of work motivation on employee performance has a very strong relationship, the nature of work motivation relationship with employee performance value (+) means that if the motivation of increasing the performance of employees in the Office of the Regional Water Company (PDAM) will Sukabumi increasing. Value of coefficient of determination (KD) of r Square = 0.501, meaning that the magnitude of the effect of work motivation (X) on employee performance (Y) of 50.1%. Regression value Y = 0.930 + 0.828 x pales work motivation up 1 point, the performance of employees rose 0.828 points, if the motivation to work up 2 points then the performance of employees rose 2 x 0.828 is equal to 1.656 with a constant value is at 0.930.